Do We Need Rights in Bioethics Discourse?. Issue 3 (9th April 2020) - Sim, Julius
Abstract: Moral rights feature prominently and are relied on substantially in debates in bioethics. Conceptually, however, duties can perform the logical work of rights, but not vice versa, and reference to rights is therefore inessential. Normatively, rights, like duties, depend on more basic moral values or principles, and attempts to establish the logical priority of rights over duties or the reverse are misguided. In practical decision making, however, an analysis in terms of duties is more fruitful than one based on rights. A right may function as a proxy term for a consequentialist rule, or for a deontological constraint, but does not thereby enrich these concepts. Rights may also help in a purely expressive sense and may assist an initial focusing on a moral conflict. However, their role in bioethics discourse is more one of convenience than of necessity. Moreover, unless rights are firmly founded on fundamental moral values, their use encourages rhetoric rather than argument.